2016
DOI: 10.1039/c6tb00730a
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional nanoplatform for lysosome targeted delivery of nitric oxide and photothermal therapy under 808 nm near-infrared light

Abstract: Nitric oxide (NO) plays important roles in various physiological and pathological processes. The development of multifunctional nanoplatforms that enable site-specific delivery of NO is expected to provide new insights toward the realization of NO-mediated therapy. We report herein a novel nanoplatform {Lyso-Ru-NO@FA@CDs}, (1), where a lysosome-targeting NO donor, Lyso-Ru-NO, and a folic-acid (FA)-directing group were incorporated into carbon dots (CDs).Nanoplatform 1 exhibited immediate NO release and a rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…Without the laser irradiation, the bacterial survival rates in the TG-NO-B-treated groups were 80.4 ± 8.3%, 84.1 ± 7.5%, and 85.5 ± 7.7% for MDR Ab, Kp and Pa, respectively, compared to the untreated controls (PBS); however, all the other groups without NIR laser irradiation (TG, TG-NO and TG-B) showed no significant changes in the percentages of survival bacteria. The slight bactericidal effects of the TG-NO-B-treated groups could be attributed to targeted and relatively small amount of NO release by TG-NO-B without NIR light [22,47]. Upon exposure to NIR laser irradiation (808 nm, 0.75 W/ cm 2 , 10 min), the TG-and TG-NO-treated groups exhibited no or very little decrease in the bacterial viabilities, due largely to no or weak binding between TG/TG-NO and the bacteria [9]; whereas the inactivated percentages in the TG-B-treated groups were 55.6 ± 9.0%, 55.2 ± 9.5 and 55.6 ± 9.0 for Ab, Kp and Pa, respectively, owing to the occurrence of targeted PTT [35].…”
Section: In Vitro Antibacterial and Anti-biofilm Activities Of Tg-no-bmentioning
confidence: 99%
“…Without the laser irradiation, the bacterial survival rates in the TG-NO-B-treated groups were 80.4 ± 8.3%, 84.1 ± 7.5%, and 85.5 ± 7.7% for MDR Ab, Kp and Pa, respectively, compared to the untreated controls (PBS); however, all the other groups without NIR laser irradiation (TG, TG-NO and TG-B) showed no significant changes in the percentages of survival bacteria. The slight bactericidal effects of the TG-NO-B-treated groups could be attributed to targeted and relatively small amount of NO release by TG-NO-B without NIR light [22,47]. Upon exposure to NIR laser irradiation (808 nm, 0.75 W/ cm 2 , 10 min), the TG-and TG-NO-treated groups exhibited no or very little decrease in the bacterial viabilities, due largely to no or weak binding between TG/TG-NO and the bacteria [9]; whereas the inactivated percentages in the TG-B-treated groups were 55.6 ± 9.0%, 55.2 ± 9.5 and 55.6 ± 9.0 for Ab, Kp and Pa, respectively, owing to the occurrence of targeted PTT [35].…”
Section: In Vitro Antibacterial and Anti-biofilm Activities Of Tg-no-bmentioning
confidence: 99%
“…In our system, proteins (such as BSA or OVA) were used to modify the Ag 2 S QDs; then, the NO donor tert-butyl nitride (TBN) could be further coupled to the proteins to form Ag 2 S@BSA-SNO nanoparticles ( Fig. 1a).We demonstrated that NO could be generated and released from the Ag 2 S QDs effectively under the NIR irradiation in vitro [43][44][45][46][47]. In the mice tumor model, Ag 2 S QDs could accumulate at the tumor site by EPR effect.…”
Section: Introductionmentioning
confidence: 90%
“…57 In recent research, there were also many combinations of ruthenium nitrosyls and carbon quantum dots to form nanomedicines, then employing NIR light to produce a photothermal effect. 58,59 Researchers have used the covalent bonding of NO donors and nanomaterials to successfully load donors and release NO at specific locations to play important physiological roles. Dr Xue et al integrated photothermal and NO release characteristics into a single nanocomposite to achieve synergistic photothermal and NO antibacterial effects.…”
Section: Encapsulating the No Donor In Nanomaterialsmentioning
confidence: 99%